More successful education of preschool teachers by consensus – the delphi method (Croatian experience) - Ljubetić, Maja (Array, 2014)
In their paper, authors address the issue of improving formal education of early childhood and preschool teachers so that students – future preschool teachers would acquire competences necessary for quality educational work with early age and preschool children and their families, and would become competitive in the labor market. In the empirical non-experimental research in which 30 scientists, experts and practitioners participated with high level of consensus, responses to seven research questions, indicating changes and their direction in the formal education of early childhood and preschool teachers, were obtained by use of the Delphi method.